Therapeutic drug monitoring of ciclosporin A and tacrolimus in heart lung transplant patients using dried blood spots. (January 2014) - Hinchliffe, Edward; Adaway, Joanne; Fildes, James; Rowan, Anna; Keevil, Brian G
Background: Therapeutic drug monitoring of ciclosporin A (CsA) and tacrolimus is traditionally performed using venous whole blood sampling. A number of reports have described development of ultra high-performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) methods for the quantitation of CsA and tacrolimus from dried blood spots (DBS), which may offer a convenient alternative. As yet, no such reports have validated this methodology using fingerprick capillary DBS samples collected from transplant patients. Methods: Capillary fingerprick DBS were collected from heart and lung transplant patients in a specialist cardiothoracic transplant centre. We utilized our previously published method for the extraction and simultaneous quantitation of CsA and tacrolimus from DBS using UPLC-MS/MS. Drug concentrations measured from DBS were compared to concentrations measured in venous whole blood by our routine clinical UPLC-MS/MS assay. Results: In total, 91 heart or lung transplant patients were enrolled onto the study; 46 patients were on CsA therapy and 45 on tacrolimus therapy. Passing–Bablock analysis demonstrated excellent agreement between capillary fingerprick DBS samples and venous whole blood samples. There was a mean positive bias of 2.6  µ g/L (95% confidence interval (CI) −2.2 to 7.5  µ g/L) for CsA ( n  = 45) and mean negative bias of −0.7  µ g/L (95% CI −1.1 to −0.3  µ g/L) for tacrolimus ( n  = 42). Conclusions: We demonstrate utility of DBS for serial monitoring of CsA and tacrolimus using UPLC-MS/MS in heart and lung transplant patients. This may offer significant advantages for these patients including the ability to take capillary DBS samples in the community prior to clinic visits.